2020
DOI: 10.1111/sji.12977
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and hepatic involvement: The liver as a main actor of the pandemic novel

Abstract: The worldwide breakdown due to novel coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has attracted the interest of the scientific community. Current research is also focusing on the liver as site of ongoing SARS-CoV-2 infection. In this review, we will summarize all data of updated literature, regarding the relationship between SARS-CoV-2 infection and liver involvement. An overview will be given on liver injury, liver transplant and the possible

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
(79 reference statements)
2
20
0
5
Order By: Relevance
“…The adipose tissue of obese patients is thought to express high levels of ACE2 and, thus potentially functions as SARS‐CoV‐2 reservoir with prolonged viral shedding time 37 . SARS‐CoV‐2 infection and the related hyperinflammatory syndrome could act as “second hit” to a simple fatty liver and trigger “acute‐on‐chronic” steatohepatitis (NASH) with elevated aminotransferases 34 . Moreover, hepatic expression of ACE2 was strongly upregulated in a high‐fat diet‐induced NASH model in rodents, 16 possibly increasing hepatic susceptibility to SARS‐CoV‐2 infection in patients with NAFLD or NASH.…”
Section: Covid‐19 In Patients With Pre‐existing Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The adipose tissue of obese patients is thought to express high levels of ACE2 and, thus potentially functions as SARS‐CoV‐2 reservoir with prolonged viral shedding time 37 . SARS‐CoV‐2 infection and the related hyperinflammatory syndrome could act as “second hit” to a simple fatty liver and trigger “acute‐on‐chronic” steatohepatitis (NASH) with elevated aminotransferases 34 . Moreover, hepatic expression of ACE2 was strongly upregulated in a high‐fat diet‐induced NASH model in rodents, 16 possibly increasing hepatic susceptibility to SARS‐CoV‐2 infection in patients with NAFLD or NASH.…”
Section: Covid‐19 In Patients With Pre‐existing Liver Diseasementioning
confidence: 99%
“…Individuals with a poorer prognosis of COVID-19 are typically older (>60) with metabolic co-morbidities such as obesity (body mass index >30 kg/m 2 ) and diabetes, a profile which is similar to those at increased risk of NAFLD. 33,34 A study from 2 COVID-19 hospitals in China compared liver function tests and clinical outcome in patients with (n = 47) and without (n = 155) NAFLD.…”
Section: Obesity and Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…Patients with COVID-19 may experience cytokine storm syndrome, with the excessive release of inflammatory mediators due to overactivation of the immune system [18]. Li et al [19] showed that elevated levels of C-reactive protein serve as a predictor of liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitous distribution of SARS-COV-2 receptor for viral entry, ACE2, on Cholangiocytes naturally points towards a hepatic injury being a common systemic manifestation of extrapulmonary COVID-19 infection 12 . Possible mechanisms that may potentially underlie this association include immune-mediated damage as a result of the severe inflammatory response commonly referred to as "the cytokine storm" 13 , direct hepatotoxicity due to viral replication in hepatic cells, anoxic damage (hypoxic hepatitis) that may accompany respiratory failure, Drug-induced liver injury (DILI) and the reactivation of a pre-existing liver disease [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%